SPECIFIC AND NON-SPECIFIC PARAMETERS BASED ON SIMPLICIA AND ETHYL ACETATE FRACTIONS OF STAR FRUIT LEAVES (AVERRHOA CARAMBOLA L.) - FITRIANI, DIAN; ELYA, BERNA; NOVIANI, ARIKA (International Journal of Applied Pharmaceutics, 2020)
Objective: Star fruit (Averrhoa carambola L.) is a plant with numerous benefits, including anti-skin inflammation properties. The aim of the present study was to evaluate simplicia and ethyl acetate fractions of star fruit leaves collected from three regions in Indonesia, including Depok, Subang, and Sukabumi, and to characterize specific and non-specific parameters. Methods: Extraction was performed through maceration. Next, liquid partitioning was performed to obtain ethyl acetate fractions. Chromatograms for simplicia and ethyl acetate fractions for samples from three regions were obtained using chloroform: methanol:water (8:2:0.5) with apigenin as the standard. Results: The yield of the ethyl acetate fraction from the star fruit leaves was 4.2–6.2%. Water content, total ash content, and acid-soluble ash contents were 4.79%, 1.55%, and 0.064%, respectively, and total flavonoid levels were 14.63–22.14 mg QE/g of a fraction. The water-soluble and ethanol-soluble extracts were 14.32% and 9.69%, respectively, and total flavonoid contents were 0.12–0.18 mg QE/g simplicia. In addition, drying losses, ash content, and acid-soluble ash content were 9.70%, 7.14%, and 0.31%, respectively. The results of solvent residues and heavy metal contaminant (Hg, Pb, Cd, and As) tests indicated that the ethyl acetate fraction did not contain solvent residue or heavy metal contamination. Conclusion: The specific and non-specific parameters based on simplicia and ethyl acetate fractions from star fruit leaves meet the requirement.